Status de mutação BRAF p.V600E em diferentes áreas microscópicas do ameloblastoma - Maria Sissa Pereira Sant'Ana (2020)
BRAF p.V600E is the most common mutation in conventional ameloblastomas and unicystic ameloblastomas. It is known that odontogenic cysts do not present this mutation and that they represent an important differential diagnosis for ameloblastomas, especially its unicystic variant. Several unicystic ameloblastoma and some odontogenic cysts, such as dentigerous and radicular cysts, share clinical and radiographic features, and may exhibit similar histological characteristics in incisional biopsies or in severely inflamed tissues, making it difficult to accurately diagnose the lesion. Different morphological areas found in ameloblastomas and the molecular characteristics of each of these regions should be investigated in order to determine whether molecular evaluation would help to establish the correct diagnosis, contributing to select the most appropriate treatment by oral surgeons. Therefore, the aim of this study was to verify BRAF mutational status in histological areas of ameloblastomas presenting different microscopic features. Five cases of ameloblastoma were analysed, with three cases classified as unicystic ameloblastoma and two cases classified as (conventional) ameloblastoma with large areas of cystic degeneration. Two or three regions exhibiting different microscopic characteristics were selected from each case and enriched by manual microdissection. qPCR or Sanger sequencing were performed to determine BRAF p.V600E status. We observed that four cases exhibited BRAF p.V600E in all different areas evaluated, while the only negative case for BRAF mutation also demonstrated negativity in all microscopic regions analyzed. Our results suggest that ameloblastomas appear to exhibit a homogeneous profile regarding BRAF p.V600E along histological regions of the tumor presenting different microscopic appearance.